NINA, PERANGKAT LUNAK PEMASARAN PRODUK MESIN PABRIK DAN MESIN PENGOLAHAN TEH BERBASIS WEB DI CV PRIMA PUTRA BANDUNG - NINA AMALIA (POLITEKNIK PIKSI GANESHA, 2018)
Marketing is an integrated communication process that aims to provideinformation about goods or services in relation to satisfying human needs and wants. Asa company engaged in the field of Industrial Engineering and machinery, CV. PrimaPutra in particular the sales department has a problem to market its products, especiallyto market products to areas outside the city of Bandung. So it takes a good marketingstrategy that can attract and reach more consumers and also can meet the needs ofconsumers.To handle the problem, then created a web-based product marketing software.The methodology used in this research is Object-oriented method or OOP (ObjectOriented Program) using the design tools such as: Usecase, Activity Diagram, andothers. While in the development of the software using CMS (Content ManagementSystem) in this case CMS used is CMS Joomla and for its database using MySql.So with the manufacture of marketing software product factory and tea processingmachine based web can help the sales to make it easier in doing marketing activities.